If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 4x + 18 Reorder the terms: 2x = 18 + 4x Solving 2x = 18 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2x + -4x = 18 + 4x + -4x Combine like terms: 2x + -4x = -2x -2x = 18 + 4x + -4x Combine like terms: 4x + -4x = 0 -2x = 18 + 0 -2x = 18 Divide each side by '-2'. x = -9 Simplifying x = -9
| 6-5(3x-2)=-14 | | X+.25X=45 | | 16x-5=2(2x+3) | | -149=10x-29 | | 4/(-1)-5 | | 6=(y-10) | | 4/(-1) | | (3x-2/4)+(x+57/7)=13 | | x4/x=2 | | 30=90/x | | (9-2y)/3=y | | 6-6r-2=16 | | 30=90 | | 3(3*x+4*y+5)+2(2*x-4*y-3)= | | 3x-2/4+x+57/7=13 | | 1.8z-1(-2+z)=1.5 | | 25x^2y^4-121= | | 4(5x-3)=68 | | 2=(x-2.7)/0.6 | | 25=-8x-87 | | 6/7=2n | | 11z+35=100 | | 2(x+3)=x+5 | | 3x=35+(-2y) | | 12/17+3/17= | | -7x+37=-3(1+5x) | | 7(8-3x)=182 | | 0.19y+0.07(y+4000)=1060 | | 5x-14=4(2x+1) | | x-4/3+4/3=-x/5 | | 2-3x=62 | | 8x^2+28x=-24 |